Pengaruh Fenomena Tren Korean Wave Dalam Perkembangan Fashion Style Di Indonesia - Muhammad Alvin Wicaksono; Annisa Patricia W; Dita Maryana (Jurnal Sosial-Politika, 2021)
The Korean wave phenomenon has taken the world by storm. Korean Wave is a term that refers to the popularity of Korean pop culture overseas. In this case, the term is used across the country to refer to the wider spread of South Korean pop culture in general or around the world. Besides KPop and Kdrama, Korean culture is also very widespread, even fans apply elements of Korean culture in their daily life. One that is very common in various parts of the world is fashion style or Korean fashion style. The world of fashion is experiencing rapid development, especially Korean fashion, which has influenced hairstyles, ways of dressing, shoes, and even makeup. Korean fashion is considered unique because it represents bright clothing colors and is easy to match with Asian bodies and skin tones. Korean fashion exists and influences its followers in their daily life. From this we can conclude how the problem of dependence on Korean fashion styles affects the behavior of the population in Indonesia.